Counterstreaming Cold H+, He+, O+, and N+ Outflows in the Plasmasphere - Krall, J.; Huba, J. D. (Frontiers in Astronomy and Space Sciences, 2021)
The Naval Research Laboratory (NRL) Sami3 is Also a Model of the Ionosphere (SAMI3) ionosphere/plasmasphere code is used to examine H+ , He+ , N+ , and O+ thermal outflows during a storm. Here, H+ and He+ outflows are associated with refilling while O+ and N+ outflows are associated with ring current heating. An improved model of counterstreaming H+ outflows from the two hemispheres is presented, using an implementation of SAMI3 with two fluid species for H+ . The two-fluid H+ model avoids nonphysical high-altitude ‘top-down refilling’ density peaks seen in one-fluid H+ simulations. Counterstreaming cold ion populations are found in all cases. In these fully three-dimensional simulations with realistic magnetosphere boundary conditions, nonphysical top-down refilling density peaks were milder than those found in previous single-field- line or single-magnetic-longitude simulations. In the present two-fluid H+ case, ‘bottom-up refilling’ density peaks were so mild as to be difficult to detect. For O+ and N+ , the nonphysical high- altitude density peak is a brief (1-2 hours) transient that occurs when heating-driven northward and southward flows first meet. In general, He+ outflows mimic H+ outflows while N+ outflows mimic O+ outflows.